Kepemimpinan dan Iklim Etis sebagai Faktor Perilaku Etis - Arpina, Yeni; ., Nurfaisal; ., Fatkhurrahman (CV. ITTC INDONESIA, 2025)
The research was conducted at the Ministry of Religious Affairs Office in Riau Province with the aim of examining the role of ethical climate in mediating the effect of ethical leadership on ethical behavior. The study population consisted of 160 individuals. Based on this population size, according to the Krejcie and Morgan table (1970), the sample size for this study was 113 individuals. The sampling method employed in this research was Systematic Random Sampling. All respondents were utilized to obtain primary data related to the variables, which were collected through a questionnaire using a 5-point Likert scale. All data obtained were analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. The study found that ethical leadership had a significant positive effect on ethical behavior; ethical leadership had a significant positive effect on ethical climate; ethical climate had a significant positive effect on ethical behavior; and ethical climate mediated the effect of ethical leadership on ethical behavior.